Knowledge management in modern organizations - Jennex, Murray E., 1956- (Hershey, PA : Idea Group Pub., 2007)
"This book discusses the philosophical foundations of knowledge management, serving as a viable resource for academicians, practitioners, researchers, and students. It also depicts a global perspective, as the authors come from Asia, Europe, the Middle East, and the United States, and adds value to any course focused on KM in organizations"--Provided by publisher.
Includes bibliographical references and index.
Keywords: Knowledge management